Research Progress and Prospect of High-Entropy Alloy Materials - Li, Tianxin; Wang, Shudao; Lu, Yiping; Cao, Zhiqiang; Wang, Tongmin; Li, Tingju (Zhongguo gong cheng ke xue (Online), 2023)
With the rapid development of world’s technological level and the urgent demand of national economic construction for high-performance alloy materials, traditional single-component alloys gradually fail to satisfy the increasing service requirements. Owing to their unique physical, chemical, and mechanical properties, high-entropy alloys are expected to play an important role in major engineering fields such as national defense, aviation, aerospace, marine, nuclear energy, medical care, and new energy, greatly expanding the design range of metal material compositions. In this paper, based on the specific demands of advanced high-entropy alloy materials in various fields, the characteristics and connotations of high-entropy alloy materials are summarized, and the overall situation and prospects of high-entropy alloy material development are analyzed, as well as the current status of high-entropy alloy development in China and abroad. On this basis, the gaps and deficiencies in the field of high-entropy alloys in China are pointed out. First, some basic raw materials of the high-entropy alloys still rely on imports, which severely threatens the security of the industrial chain. Second, the research and development investment in industrial application of high-entropy alloys needs to be increased, and the industrial–academia–research–application system of high-entropy alloys is not yet sound. Regarding the above-mentioned issues, this study proposes the following policies and measures: strengthening the top-level design of high-entropy alloy material research and development while improving industrial policies; strengthening the connection and communication between enterprises and research institutes; improving the standardization, testing, characterization, and evaluation systems of high-entropy alloy materials; advancing the construction of talent teams; and reducing material costs and creating high value-added products, to promote the systematic, green, high-end, and intelligent development of China’s advanced high-entropy alloy material industry.